(untitled) (Human Factors in Design, 2012)
This article presents the results related to an Ergonomic Work Analysis carried out with street sweepers in the city of Florianópolis/SC, Brazil. The RULA Protocol, by McAtamney & Corlett (1993), as well as the study of Inertial Properties of the Body, by Riehle (1979), were used as tools of ergonomic and biomechanical analysis, in order to subsidize proposals to improve the management of the working environment analyzed.